The Bifidogenic Effect Revisited-Ecology and Health Perspectives of Bifidobacterial Colonization in Early Life - Kumar Himanshu; Collado Maria C.; Wopereis Harm; Salminen Seppo; Knol Jan; Roeselers Guus (MDPI, 2025)
Extensive microbial colonization of the infant gastrointestinal tract starts after parturition. There are several parallel mechanisms by which early life microbiome acquisition may proceed, including early exposure to maternal vaginal and fecal microbiota, transmission of skin associated microbes, and ingestion of microorganisms present in breast milk. The crucial role of vertical transmission from the maternal microbial reservoir during vaginal delivery is supported by the shared microbial strains observed among mothers and their babies and the distinctly different gut microbiome composition of caesarean-section born infants. The healthy infant colon is often dominated by members of the keystone genus Bifidobacterium that have evolved complex genetic pathways to metabolize different glycans present in human milk. In exchange for these host-derived nutrients, bifidobacteria's saccharolytic activity results in an anaerobic and acidic gut environment that is protective against enteropathogenic infection. Interference with early-life microbiota acquisition and development could result in adverse health outcomes. Compromised microbiota development, often characterized by decreased abundance of Bifidobacterium species has been reported in infants delivered prematurely, delivered by caesarean section, early life antibiotic exposure and in the case of early life allergies. Various microbiome modulation strategies such as probiotic, prebiotics, synbiotics and postbiotics have been developed that are able to generate a bifidogenic shift and help to restore the microbiota development. This review explores the evolutionary ecology of early-life type Bifidobacterium strains and their symbiotic relationship with humans and discusses examples of compromised microbiota development in which stimulating the abundance and activity of Bifidobacterium has demonstrated beneficial associations with health.